Evaluation of X Coffee Shop in Bogor Compensation with Determination of Position Grade Using Overlapping and Adhered Methods - Dhiya Abiddaya; Fadhli Hidayat; Frans Frans; Lintang Dwiansyah; M. Rifal Agung Permana; Lindawati Kartika (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Over the last few years, coffee shops have gained immense popularity as a travel destination for individuals looking for a relaxed atmosphere to relax and enjoy their preferred coffee blend.One of the most effective ways to achieve business success is to offer competitive salary packages that are in line with employee expectations and market norms.In this study, we aim to evaluate the compensation practices of Genus Coffee Shop, a leading player in the industry, using adhered and overlapping methods to rank positions.This study will explore the benefits offered to employees in various positions, including supervisors, cashiers, and baristas in coffee shops. In addition, this study will assess the state of the external market and how wage rates are affected. This study uses a descriptive method with a qualitative approach to reveal compensation management at the UKM X coffee shop in Bogor. Data collection was carried out using interview instruments. The location of this research was conducted at UKM X Coffee Shop in the Bogor area. This research was conducted from January to February 2023. The people in the study were the Cafe Managers of UKM X Coffee Shop and all employees of UKM X Coffee Shop. After analyzing and improving the payroll system, it can be concluded that the compensation system is effective to be implemented by X Coffee shop is to use Adhered method. This is because operational costs are lower.